Diversionary conflict: Demonizing enemies or demonstrating competence?. (July 2017) - Haynes, Kyle
How do embattled leaders hope to secure their hold on power by initiating conflict abroad? The literature on diversionary war has emphasized two distinct mechanisms by which leaders stand to gain from conflict — the "rally around the flag" and "gambling for resurrection" theories. But despite a massive literature on the subject, these competing theories of diversionary incentives have never been subjected to comparative empirical evaluation. This article seeks to fill this gap. I argue that the rally and gambling theories predict diversionary conflicts to target different types of states. Diversionary conflicts driven by a rally logic will target traditional enemies and out-groups, including rivals, neighbors, and geopolitically incompatible states. Gambling for resurrection, on the other hand, pushes leaders to target powerful states in order to demonstrate competence to their constituents. Challenging the conventional wisdom, I find little evidence to support the rally mechanism. The results offer substantial support for the gambling for resurrection theory, indicating that diversionary conflict may be primarily driven by unpopular leaders attempting to prove their competence domestically.